Accounting for bitcoins in light of IFRS and tax aspects - Marta Cristina Pelucio-Grecco; Jacinto Pedro dos Santos Neto; Diego Constancio (Revista Contabilidade & Finanças, 2020)
Abstract This essay presents recommendations in regard to accounting for operations that involve bitcoins, in compliance with the International Financial Reporting Standards (IFRS), and analyzes their main tax aspects. There is no specific pronouncement on the part of the International Accounting Standards Board (IASB) or from the Brazilian Accounting Pronouncements Committee (CPC) regarding the accounting treatment to be applied in operations that use these currencies. Bitcoin is of interest to economists as a virtual currency with the potential to disrupt existing payment systems and even monetary systems. This essay offers a contribution for standard-setters and the tax authority (fisco) by providing the basis for possible guidelines to be issued on the accounting treatment of bitcoin operations, as well as by defining the appropriate tax treatment; in addition, it makes a contribution for accounting professionals by suggesting the accounting policy to be adopted in these operations. Here, the analysis of the characteristics of bitcoins is compared with the guidelines and concepts of IFRS, in order to elaborate the recommendation for accounting treatment, and it suggests that the most adequate procedure would be that of foreign currency, which would go against the tax treatment adopted up until now by the Brazilian Internal Revenue Service (Receita Federal) or the Internal Revenue Service (IRS) of the United States of America (USA), which suggest treating virtual currencies as goods and not as currencies. It warrants mentioning that this contradiction may cause tax risks for taxpayers.